Development of an interdisciplinary microtia‐atresia care model: A single‐center 20‐year experience. Issue 6 (16th November 2022) - Patel, Krupa R.; Benchetrit, Liliya; Ronner, Evette A.; Occhiogrosso, Jessica; Hadlock, Tessa; Shaye, David; Quesnel, Alicia M.; Cohen, Michael S.
Abstract: Objectives: Microtia and aural atresia are congenital ear anomalies with a wide‐ranging spectrum of phenotypes and varied functional and psychosocial consequences for patients. This study seeks to analyze the management of microtia‐atresia patients at our center over a 20‐year period and to propose recommendations for advancing microtia‐atresia care at a national level. Methods: We performed a retrospective analysis of data from patients presenting to the Massachusetts Eye and Ear (Boston, MA) for initial otolaryngology consultation for congenital microtia and/or aural atresia between 1999 and 2018. Results: Over the 20‐year study period, 229 patients presented to our microtia‐atresia center at a median age of 7 years. The severity of microtia was most commonly classified as grade III ( n = 87, 38%), 61% ( n = 140) of patients had complete atresia, the median Jahrsdoerfer grading scale score was 6 (range 0–10), and 81 patients (35%) underwent surgery for microtia repair. For hearing rehabilitation, 30 patients (64%) underwent bone conduction device implantation and 17 patients (36%) underwent atresiaplasty. The implementation of an interdisciplinary, longitudinal care model resulted in an increase in patient (r = 0.819, p < .001) and surgical volume (microtia surgeries, r = 0.521, p = .019; otologic surgeries, r = 0.767, p < .001) at our center over time. Conclusion: An interdisciplinary team approach to microtia‐atresia patient care may result in increased patient volume, which could improve aesthetic and hearing outcomes over time by concentrating care and surgical expertise. Future work should aim to establish standardized clinical consensus recommendations to guide the creation of high‐quality microtia‐atresia care programs. Level of Evidence: 4. Abstract : The care of patients with microtia and aural atresia is significantly fragmented across the nation. In this paper, we analyze the clinical characteristics and management of microtia‐atresia patients at our center over a 20‐year period, describe our current interdisciplinary patient‐care model and propose recommendations for the advancement of microtia‐atresia care at a national level.